Marketing Channels: Relationships and Performance - PELLEGRINI, Luca (Institutional Knowledge at Singapore Management University, 1986)
Some of the papers presented at the Third International Conference on Distribution held at Angera, Italy, April 19 and 20, 1985, sponsored by the Centro di studi sul commercio of the Università Bocconi, Milan, and the Institute of Retail Management, New York University.